Enhanced detection services for developmental dysplasia of the hip in Scottish children 1997-2013 - McAllister, David A.; Morling, Joanne R.; Fischbacher, C.A.; Reidy, M.; Murray, A.; Wood, R. (BMJ, 2018)
Background